Genetics of movement disorders - Pulst, Stefan-M (Academic Press, 2003)
Hereditary or genetic diseases featuring involuntary movements constitute a major aspect of the practice of neurology, functional neurosurgery, genetics, and many areas of basic and applied neuroscience research. Describing the current knowledge on these disorders, Genetics of Movement Disorders brings together information essential for clinicians, geneticists, and neuroscientists in one source. Utilizing a convenient and accessible format, the book is designed to allow easy identification of relevant information, with the overall organization of topics following established phenotypic classifications of movement disorders such as Parkinsonian syndromes, chorea, ataxia, and major categories of diseases grouped by gene locus. This book broadly appeals to neurologists, neuroscientists, geneticists, as well as cell and molecular biologists and hematologists. Key Features * Consistently formatted to present a clinical description of the disorder, followed by an in-depth analysis of the mutation and function of the mutated gene including cellular and animal models * Emphasizes the use of DNA tests for each respective disorder * Provides up-to-date, easily accessible information for clinicians, geneticists, and neuroscientists.